An evolutionary based framework for many-objective optimization problems. Issue 4 (10th July 2018) - Bazargan Lari, Kimia; Hamzeh, Ali
Abstract : Purpose: Recently, many-objective optimization evolutionary algorithms have been the main issue for researchers in the multi-objective optimization community. To deal with many-objective problems (typically for four or more objectives) some modern frameworks are proposed which have the potential of achieving the finest non-dominated solutions in many-objective spaces. The effectiveness of these algorithms deteriorates greatly as the problem's dimension increases. Diversity reduction in the objective space is the main reason of this phenomenon. Design/methodology/approach: To properly deal with this undesirable situation, this work introduces an indicator-based evolutionary framework that can preserve the population diversity by producing a set of discriminated solutions in high-dimensional objective space. This work attempts to diversify the objective space by proposing a fitness function capable of discriminating the chromosomes in high-dimensional space. The numerical results prove the potential of the proposed method, which had superior performance in most of test problems in comparison with state-of-the-art algorithms. Findings: The achieved numerical results empirically prove the superiority of the proposed method to state-of-the-art counterparts in the most test problems of a known artificial benchmark. Originality/value: This paper provides a new interpretation and important insights into the many-objective optimization realm by emphasizing on preserving the population diversity.